2014
DOI: 10.11560/jahp.27.1_45
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive appraisal of interpersonal stress and social skills in childcare workers

Abstract: Cognitive appraisal of interpersonal stress in childcare workers was investigated from the perspective of interpersonal stress situations and social skills. Participants were kindergarten teachers n 57 and nursery teachers n 91. ey responded to the Stress Cognitive Appraisal Scale and Kikuchi s Scale of Social Skills. Results indicated that dealings with parents and children were considered important sources of interpersonal stress, whereas dealings with superiors at the workplace were considered more di cult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These results suggest that the degree to which these women believe they have the ability to effectively communicate with their main sexual partners is crucially related to sexual risk vulnerability. All three psychological factors involve symptoms that reduce ability and motivation to interact effectively in interpersonal relationships (Motoyoshi & Hosono, 2014; Segrin et al, 2007). For example, Caprara and colleagues (2010) found that interpersonal and social self-efficacy predicted one’s ability to resist peer pressure.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the degree to which these women believe they have the ability to effectively communicate with their main sexual partners is crucially related to sexual risk vulnerability. All three psychological factors involve symptoms that reduce ability and motivation to interact effectively in interpersonal relationships (Motoyoshi & Hosono, 2014; Segrin et al, 2007). For example, Caprara and colleagues (2010) found that interpersonal and social self-efficacy predicted one’s ability to resist peer pressure.…”
Section: Discussionmentioning
confidence: 99%